Farmer's satisfaction on mechanized rice tranplanter a case study in Kampung Sg Leman, Sekinchan Sabak Bernam / Mohd Syahrul Nizam Abdul Aziz - Abdul Aziz, Mohd Syahrul Nizam (Faculty of Plantation and Agrotechnology, 2016)
The rice transplanter machine is designed planting seedlings into the paddy fields. Transplanter machine can reduce the labour force and reduce the time of planting seedlings. By using transplanter it can help streamline of rice seedling growth and yield, uniform the row of planting seed. In addition, the seedlings are planted with transplanter machine growth in a nursery first. This study aims to determine the level of satisfaction of farmers to plant rice transplanter. Therefore, a study was conducted in 80 by farmers in Kampung Sungai Leman, Sekinchan, Sabak Bernam. The results of the factor analysis revealed two factors was selected from farmers. from the six factors, which is the quality of the seedlings and size of transplanter. Another four factors such as soil density, price engines, engine efficiency and operation were less concerned with farmer's satisfaction when using the transplant.